Public Participation of Renewable Energy (PPRED) Model in Malaysia: An Instrument Development - Wan Abdullah, W Muhammad Zainuddin B; Zainudin, Wan Nur Rahini Aznie Bt; Mohamad Ishak, Waznatol Widad Bt; Sulong, Farizah Bt; Zia Ul Haq, Hafiz Muhammad (International Journal of Renewable Energy Development, 2021)
Lack of an established measuring instrument for public participation towards renewable energy (RE) development has become a crucial concern for the researchers. Therefore, this research aims to develop and validate the instruments that measure public participation towards renewable energy development (PPRED) in Malaysia. This study incorporates degree of knowledge on RE (KRE), environmental concern (EC), public awareness on RE (ARE), attitude towards RE usage (AURE), and willingness to adopt RE technology (WTA) in the PPRED model, with an aim to predict public willingness to pay (WTP) for energy generated from RE sources. Using data of 172 usable responses, this study conducts an exploratory factor analysis (EFA) to analyse the factor structures. In addition to this, using data from 154 usable responses from a second sample frame, this study also conducts confirmatory factor analysis (CFA) to examine the unidimensionality of the measurement model. Correlations are used to measure discriminant and convergent validation of the items whereas Cronbach’s Alpha is used to measure internal consistency among different items. Specifically, EFA is used for variable extraction and CFA is used to test dimensionality, validity, and reliability of the PPRED model. The results proved validation of the PPRED model, indicating that all instruments included are reliable and valid to be used in the research. This study is also pertinent to initiate targeted campaigns and public education policies to improve awareness among Malaysians relating to renewable energy development